2021
DOI: 10.7150/thno.51390
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor precursor in the immune system is a novel target for treating multiple sclerosis

Abstract: Rationale: Brain-derived neurotrophic factor precursor (proBDNF) is expressed in the central nervous system (CNS) and the immune system. However, the role of proBDNF in the pathogenesis of multiple sclerosis (MS) is unknown. Methods: Peripheral blood and post-mortem brain and spinal cord specimens were obtained from multiple sclerosis patients to analyze proBDNF expression in peripheral lymphocytes and infiltrating immune cells in the lesion site. The proBDNF expression profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 19 publications
2
45
4
Order By: Relevance
“…We also observed that an intraperitoneal injection of mAb-proBDNF highly alleviated the fear conditioning memory in SAE mice, which was accomplished by perturbing the peripheral proinflammatory response (Luo et al, 2020). In our latest study, we confirmed that mAb-proBDNF treatment can attenuate multiple sclerosis in a mouse model and inhibit the proinflammatory response in the spinal cord and spleen of diseased mice (Hu et al, 2021). In the current study, our results showed that both intrahippocampal microinjection (Figure 4) and the systemic delivery (Figure 5) of mAb-proBDNF improved the cognitive impairment in SAE mice, this may be due to the inhibition of the inflammatory response of the CNS and/or peripheral system.…”
Section: Discussionsupporting
confidence: 63%
“…We also observed that an intraperitoneal injection of mAb-proBDNF highly alleviated the fear conditioning memory in SAE mice, which was accomplished by perturbing the peripheral proinflammatory response (Luo et al, 2020). In our latest study, we confirmed that mAb-proBDNF treatment can attenuate multiple sclerosis in a mouse model and inhibit the proinflammatory response in the spinal cord and spleen of diseased mice (Hu et al, 2021). In the current study, our results showed that both intrahippocampal microinjection (Figure 4) and the systemic delivery (Figure 5) of mAb-proBDNF improved the cognitive impairment in SAE mice, this may be due to the inhibition of the inflammatory response of the CNS and/or peripheral system.…”
Section: Discussionsupporting
confidence: 63%
“…EAE is histologically and clinically similar to MS, which was established in an animal model to study autoimmune demyelination ( 11 , 39 ). Myelin-reactive T cells of the CNS produce and release BDNF to promote post-traumatic tissue repair ( 39 ).…”
Section: Bdnf In Autoimmune Inflammatory Diseasesmentioning
confidence: 99%
“…Of note, transfection of T cells expressing BDNF strongly reduced brain damage in EAE and protected axons ( 40 ). Elevated serum BDNF levels have also been associated with nerve repair in patients with MS ( 11 ).…”
Section: Bdnf In Autoimmune Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of proBDNF in CD4 + T cells regulates sepsis-associated encephalopathy ( 25 ). Recently, we reported that proBDNF-p75 NTR signaling is up-regulated in the lymphocytes of both patients with multiple sclerosis (MS) and in experimental autoimmune encephalomyelitis (EAE) mouse models ( 26 ); a monoclonal antibody against proBDNF (McAb-proB) was found to attenuate clinical scores, limit demyelination, and inhibit proinflammatory cytokines in EAE mice ( 26 ). These results suggest that proBDNF signaling released from B cells may implicate into the pathogenesis of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%